2018
DOI: 10.3238/arztebl.2018.0243
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarettes and the Use of Conventional Cigarettes

Abstract: Among adolescents who have never smoked, experimentation with conventional cigarettes is more common in those who have used e-cigarettes. This effect seems to be stronger among adolescents who, in general, have a lower risk of starting to smoke. The 6-month observation period of this study is too short to allow any inference regarding a connection between e-cigarette use and the development of tobacco dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 45 publications
0
57
1
5
Order By: Relevance
“…Since the time that we published our earlier analysis [8] and our paper on general considerations relating to vaping as a possible gateway into cigarette smoking [7] a number of other authors have presented evidence from prospective studies [9][10][11][12][13][14][15]. The studies vary in the extent to which potential confounding variables have been adjusted for, with large OR estimates tending to be reported in studies with more limited control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the time that we published our earlier analysis [8] and our paper on general considerations relating to vaping as a possible gateway into cigarette smoking [7] a number of other authors have presented evidence from prospective studies [9][10][11][12][13][14][15]. The studies vary in the extent to which potential confounding variables have been adjusted for, with large OR estimates tending to be reported in studies with more limited control.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a US study [14] ,which reported an OR of 6.8 (1.7-28.3), following adjustment for ten covariates independently associated with initiation of smoking, most of the other studies which appear to have better control for confounding gave lower estimates. These included a study in Taiwan [10] which reported an OR of 2.14 (1.66-2.75), a study in Germany [12] which reported an OR of 2.18 (1.65-2.87) and a study in Finland [11] which reported that adjustment reduced the OR from 11.52 (4.91-26.56) to 2.92 (1.09-7.85). Notably, a study in Great Britain [16] reported an OR of 11.89 (3.56-39.72) estimated using the usual logistic method, but a reduced value of 1.34 (1.05-1.72) using causal mediation analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there were studies underlining the influence of sensation seeking behaviour (defined as "the search for changing and novel experiences to feel intense sensations again and again") and e-cigarette use (Morgenstern et al, 2018;Nădăşan, Pénzes, & Urbán, 2017;Hanewinkel & Isensee, 2015).…”
Section: B Behavioural Factorsmentioning
confidence: 99%
“…Bei einer Gesamtbewertung der Auswirkungen der E-Zigarette auf die Gesundheit der Bevölkerung darf zudem nicht außer Acht gelassen werden, dass E-Zigaretten einer Re-Normalisierung des Rauchens Vorschub leisten könnten und mehr als ein Dutzend Kohortenstudien, darunter auch eine Studie aus Deutschland [6], übereinstimmend zu dem Ergebnis kommen, dass E-Zigaretten Jugendliche zum Experimentieren mit Tabakzigaretten verführen können.…”
unclassified